Evaluating the center of gravity of dislocations in soccer players with and without reconstruction of the anterior cruciate ligament using a balance platform (Clinics, 2009)
OBJECTIVE: The objective of this study was to compare the dislocation of the center of gravity and postural balance in sedentary and recreational soccer players with and withoutanterior cruciate ligament (ACL) reconstruction using the Biodex Balance System (BBS). METHOD: Sixty-four subjects were divided into three groups: a) soccer players who were post- anterior cruciate ligament reconstruction; b) soccer players with no anterior cruciate ligament injuries; and c) sedentary subjects. The subjects were submitted to functional stability tests using the Biodex Balance System. The instability protocols used were level eight (more stable) and level two (less stable). Three stability indexes were calculated: the anteroposterior stability index, the mediolateral stability index, and the general stability index. RESULTS: Postural balance (dislocation) on the reconstructed side of the athletes was worse than on the side that had not undergone reconstruction. The postural balance of the sedentary group was dislocated less on both sides than the reconstructed knees of the athletes without anterior cruciate ligament injuries. There were no differences in postural balance with relation to left/right dominance for the uninjured athletes and the sedentary individuals. CONCLUSION: The dislocation of the center of gravity and change in postural balance in sedentary individuals and on the operated limb of Surgery Group are less marked than in the soccer players from the Non Surgery Group and on the non-operated limbs. The dislocation of the center of gravity and the change in postural balance from the operated limb of the soccer players is less marked than in their non-operated limbs.